The financial development-renewable energy consumption nexus in Africa: Does governance quality matter? - Toyo Amegnonna Marcel Dossou; Dossou K. Pascal; Emmanuelle Ndomandji Kambaye; Simplice Asongu; Alastaire Sèna Alinsato (African Governance and Development Institute (AGDI), 2024)
Although the impact of financial development on renewable energy consumption has been extensively examined in recent years, the study regarding the moderation of governance quality on the financial development on renewable energy consumption nexus is sparse. By filling the gap in the energy economics literature, this study investigates the moderating effect of governance quality on the relationship between financial development on renewable energy consumption for a panel of 33 African countries over the period 2000-2020. The fully modified ordinary least square (FMOLS) estimation techniques has been used to account for the cointegration and cross-sectional dependence, respectively. The results unveil that the impact of governance quality and financial development on renewable energy consumption is negative and statistically significant. Moreover, the results reveal that the FD-governance quality interactions are significant and negative. Governance quality thresholds at which the negative incidence of financial development on renewable energy consumption is completely nullified are 0.825; 2.15; 2.86; 3.52;3.36; and 0,1, respectively.
Keywords: 330; Financial development; renewable energy consumption; governance quality; Africa